Surgical Results of Anteromedial Plate Osteosynthesis for Diaphyseal Humerus Fracture - Ujjawal Pradhan; S. G. Thejaswi; H. Papa Naik; Sunil Baliga; Nobin Kumar Sharma; Avik Chakravorty (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Humeral shaft fracture management has always been controversial. There are proponents for both conservative and operative management with intramedullary nailing as well as plate osteosynthesis. Anteromedial plating of shaft fractures has not been regularly described. This study was conducted to evaluate the viability of anteromedial plating as an alternative to anterolateral and posterior plating for diaphyseal humerus fractures. Materials and Methods: The study was conducted at a tertiary care center. Inclusion criteria comprised: age more than 18 years, and diaphyseal humerus fracture treated with anteromedial plating using the anterolateral approach with a minimum follow-up of 6 months. Exclusion criteria included: pathological fracture, grade open III fractures, nonunion, intra-articular fractures, preoperative radial nerve palsy, nonconsent, and loss to follow-up. Functional outcome was evaluated at 6 months using the QuickDASH score. Results: Out of 44 volunteers, 28 (64%) were male and 16 (36%) were female. The mean age of the volunteers was 36 ± 13 years. The most common fracture type encountered was 12-A2 (41%). The mean operative time was 61.27 ± 10.3 min, and the mean perioperative blood loss was 308 cm3. The mean time for the radiological union was 13.9 weeks. One patient developed postoperative radial nerve palsy. The mean DASH score at 6 months was 13.5 ± 3.2. Conclusion: Anteromedial plating humerus using anterolateral approach provides a safe and viable alternative to lateral and posterior plating with regard to operative time, perioperative blood loss, complications, and functional recovery.